(3TQM GdYRj aj GdJUQjas - (3GdJaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg, J(B793(3g`s
(3ChdgG (B:s
(3GYde Cf GdJUQja hgh JaYjd ef GdUQa hGdaQb HjfgeG XGgQ hGdeQGO HGdJUQja ggfG ZjQ Yde GdJUQja GdPj gh eYQaI CMhGd GdCHfjIs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3ehVYG HGdaJM bGd GdTGYQ Ydi eG QhGg GdcSGQ aCUHM GdYjf RchQG Ydi GdChKGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 219s
(3eYLe GdeDdajf(B: 3 / 849s
(3cTa GdXfhf(B: 2 / 1139s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdUQas